Interrelationships of climate adaptation and organizational learning: Development of a measurement model - Fischer, Sophie; Göhlich, Michael; Schmitt, Jan (Journal of Pedagogical Research, 2022)
Climate adaptation and learning support organizations in dealing with the current and projected consequences of climate change by recognizing challenges as opportunities, ensuring business continuity and increasing their economic efficiency. Beside material resources, climate adaptation requires knowledge, technical expertise, and learning capacity. Our contribution examines the interrelationship between climate adaptation and organizational learning, as the consideration of climate adaptation in the long term and with respect to organizational learning or realignment is still represented very little in research. Thus, we conduct a regional study to analyze to what extent the companies already have climate-related structures conducive to learning, to what extent they take responsibility in terms of the learning object (climate change), and which elements prove to be limiting here. The survey of 288 companies and handicraft companies illustrate that intangible resources such as a sense of responsibility, executives’ positive attitude and common values have a significant influence on the way companies deal with climate change. Executives characterize key actors for organizational goal setting, strategic development, and functional process monitoring. The study shows that the number of climate-related measures taken increases due to higher resource capacities. As we draw conclusions about changing learning requirements, conditions, and mediums in the face of climate change, findings can provide relevant inspiration for scholars or practitioners to perceive climate adaptation as a valuable and strategic challenge to enhance the organization’s resilience per se.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Climate adaptation; Corporate social responsibility; Organizational development; Organizational education; Organizational learning